Absence of right common carotid artery in a patient with common origin of the innominate artery and left common carotid artery - Guarinello, Giovanna Golin (J Vasc Surg Cases Innov Tech, 2020)
A 50-year-old woman was referred to the noninvasive vascular laboratory for carotid artery evaluation because of a bruit in the neck. Color Doppler ultrasound examination demonstrated absence of the right common carotid artery and parallel internal and external carotid arteries originating at the brachiocephalic trunk. Computed tomography angiography further described anomalous anatomy, demonstrating a common origin of the innominate artery and left common carotid artery. Knowledge of such unusual anatomy may become valuable in future evaluation or treatment of this patient.